2020
DOI: 10.1111/dth.13887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum FoxO1 , mTORC1 , IGF ‐1, IGFBP ‐3 levels, and metabolic syndrome components in patients with acne vulgaris: A prospective case‐control study

Abstract: Recently, insulin-like growth factor-1 (IGF-1), forkhead box transcription factor (Fox) O1, and mechanistic target of rapamycin complex 1 (mTORC1) signaling have been introduced as key elements in acne pathogenesis. The aim of this study is to investigate the relationship between serum levels of IGF-1, insulin-like growth factor binding protein-3 (IGFBP-3), FoxO1 and mTORC1, and the components of metabolic syndrome (MS) and AV. This prospective case-control study was carried out on 89 participants, including 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Several studies presented different results about the relationship between the acne and the IGF-1 levels. Aktaş et al 12 found serum IGF-1 levels higher in the acne group compared to the control group in their study, and Saleh et al 13 reported that there is a significant correlation between acne severity and IGF-1 levels. They showed elevation of serum IGF-1, which enhanced androgen hormone production and the development of acne.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies presented different results about the relationship between the acne and the IGF-1 levels. Aktaş et al 12 found serum IGF-1 levels higher in the acne group compared to the control group in their study, and Saleh et al 13 reported that there is a significant correlation between acne severity and IGF-1 levels. They showed elevation of serum IGF-1, which enhanced androgen hormone production and the development of acne.…”
Section: Discussionmentioning
confidence: 75%
“…The relationship between IGF1 and acne remains controversial. Some studies reported that IGF1 levels were increased in acne patients (Agamia et al, 2016), while others showed no significant difference in IGF1 levels between acne patients and controls (Cappel et al, 2005;Aktas Karabay et al, 2020). Moreover, Vora et al (2008) found that serum IGF1 levels were positively correlated with facial sebum excretion and acne lesion counts.…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, growth hormone (GH) levels rise dramatically, followed by the release of IGF-1. IGF-1 stimulates the secretion of androgens by the adrenal and gonadal glands and also affects the sebaceous gland by the GF-1/AKT/mTORC1/SREBP1 signaling pathway [55]. This pathway leads to an increase in testosterone conversion to 5-DHT (which has a higher affinity for AR), an increase in end-organ receptor irritability to androgens, and an increase in PPAR expression [56].…”
Section: Insulin-like Growth Factor-1 (Igf-1)mentioning
confidence: 99%